The cost of reducing greenhouse gas emissions in shipping - Tristan Smith (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
The shipping sector will need to reduce its greenhouse gas emissions significantly over the coming decades in order to align them with the Paris Climate goals. How could this be achieved? What will it cost to bring down the sector's emissions? Will these costs shift maritime trade flows? This paper offers answers to these questions and identifies areas for further investigation.
Keywords: 330; Treibhausgas-Emissionen; Internationale Klimapolitik; Kostenmanagement; Frachtschifffahrt